Environmental compliance and sustainability : global challenges and perspectives - Rogers, Daniel T. (Daniel Timothy), 1959- (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
This book provides a critical understanding of the challenges that exist in protecting the local and global environment through compliance efforts using existing environmental regulations. The best compliance measures with the most useful regulations from over 50 countries are surveyed and are combined with science-based quantitative analysis of geology, hydrogeology, and the chemistry of contaminants from anthropogenic sources. The results are presented as a model that establishes a means by which protection of the environment can be greatly improved. This is accomplished through a deeper understanding of our natural world and how anthropogenic activities and their management affect our planet. Features The first book that examines the successes of environmental regulation worldwide and highlights the areas that need improvement Presents a tested and verified scientific model for enhanced environmental protection with scalability from local parcels to global levels Describes and integrates the importance of understanding the geologic and hydrogeologic environment of urban and developed areas Explains the importance of understanding the different types of pollution and their behavior in the environment Identifies the need for consistency in banning chemicals that are harmful in not just one country but throughout the world
1. Compliance and Sustainability Overview and Themes Part One: Pollution and Its Behavior 2. Pollution 3. The Behavior of Pollution in Nature 4. Geologic Vulnerability 5. Pollution Risk Factors Part Two: Environmental Regulations 6. Environmental Regulations and Pollution of the United States 7. Environmental Regulations and Pollution of the World Part Three: Compliance and Sustainability 8. Fundamental Concepts of Environmental Compliance 9. Fundamental Concepts of Sustainability 10. Building and Implementing a Model for Sustainability
OCLC-licensed vendor bibliographic record.
Keywords: Environmental protection; LAW / Environmental; NATURE / Environmental Conservation & Protection; SCIENCE / Environmental Science